Let's go to lunch!: informal client contacts by consultants in the UK. (27th August 2010) - Taminiau, Yvette; Berghman, Liselore
This exploratory study describes the importance of informal client contacts for consultants in the UK. From the consultant's perspective it is crucial to build a trustful and deep relationship with clients in order to ensure long-term survival of their firms. This is done through a strategic use of informal activities (such as enjoying sports together or a cultural event) and settings (lunches, restaurants and pubs). Based on interview data of consultants in the UK, this study shows consultants' perspectives on how they have to move smoothly in informal spaces although this can sometimes result in unsettling situations.